Effect of drought on Oryza glaberrima rice accessions and Oriza glaberrima derived-lines - Ndjiondjop, Marie-Noel; Seck, P.A.; Lorieux, Mathias; Futakuchi, K.; Yao, KN; Djedatin, G.L.; Sow, ME; Bocco, R.; Cisse, F.; Fatondji, B (Science Alert, 2012)
Rice varieties response to drought has been extensively studied and many lines have been released, but identifying new tolerant lines is still a challenge for scientists due to the complexity and the specificity of this constraint over environments. Three sets of field experiments were conducted between 2006 and 2008 at Africa Rice Center research station, Togoudo, Benin to evaluate the effect of drought on some traits of rice (Oryza sp.). Three genotype types including 202 interspecific lines, from a cross between WAB56-104 (O. sativa subsp. japonica) and CG14 (O. glaberrima), adapted to upland conditions, 60 chromosome segment substitution lines made for lowland conditions and 211 accessions of O. glaberrima Steud., were evaluated using a split plot design replicated twice or thrice and an alpha lattice design with four blocks. There was a consistent negative effect of drought on plant height and grain yield across genotypes drought-tolerance levels and across genotype/types. Plant height and grain yield were more reduced for sensitive genotypes than for moderately tolerant and tolerant genotypes. Flowering and maturity were consistently delayed across genotype types and tolerance levels. Mean delays of 6.5, 21.8 and 9.4 days were observed for start, 50 and 100% flowering, respectively. Maturity was also delayed, with consistency across genotype types. However, no clear picture of drought effect on flowering and maturity was observed in terms of differences among drought-tolerance levels. The effects of drought on the number of tillers and on leaf temperature were not consistent. Plant height and grain yield showed the clearest differences between genotype-tolerance levels. Genotypes 151-3-8, 104-3-5, 116-2-4, 117-2-6, MPL-15-3, MPL-202-3, SENL-21-2, SENL-10-1, SENL-17-2, SENL-26-3, TOG5691, TOG6679 and TOG5591 yielded higher than the parents and checks.